Curriculum Management in Traditional Islamic Boarding Schools: An Integrative Model from Salafi Dayahs - M. Nasir; Candra Wijaya; Yusuf Hadijaya (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze the management of the dayah curriculum in Islamic educational institutions through a multi-site study of two Salafi dayahs. This study uses a qualitative approach with a multi-site study design. The research data were obtained through in-depth interviews, observations, and document studies, and then analyzed using single-site and cross-site analyses. The results show that the dayah curriculum management at both sites is implemented systematically, directed, hierarchically, and continuously while remaining grounded in the classical Islamic scientific tradition. The curriculum implementation integrates the transmission of religious knowledge with the development of students' character and morals through the methods of talaqqi, bandongan, sorogan, memorization, and musyāfahah. Curriculum management plays a role in maintaining the quality of graduates, maintaining the continuity of the classical Islamic scientific tradition, and strengthening the epistemological identity of the Salafi dayahs. The organization of the curriculum is supported by the division of teaching staff tasks based on competence, experience, and scientific sanad, as well as orderly institutional governance. Learning evaluation was conducted comprehensively through oral practice, mastery of traditional Islamic texts, moral assessment, and non-academic evaluation procedures. This research yielded an integrative Salafi Islamic boarding school curriculum model built on five main components: planning, implementation, organization, management, and evaluation of learning, united by the core values of traditional Islamic texts, a chain of scientific transmission, etiquette, discipline, and responsibility.